2019
DOI: 10.1097/brs.0000000000003151
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vertebral Fracture and Diffuse Idiopathic Skeletal Hyperostosis

Abstract: Study Design. Retrospective case-control study. Objective. To investigate the prevalence and characteristics of diffuse idiopathic skeletal hyperostosis (DISH) in vertebral fracture patients admitted to our hospital. Summary of Background Data. Although vertebral fracture is generally treated conservatively with rest and use of a corset, surgery with rigid internal fixation is recommended for vertebral fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
20
1
Order By: Relevance
“…As for treatment, early surgical fixation is recommended in patients with DISH-associated fractures complicated by neurological deficits or if instability is obvious or confirmed by additional stress imaging to avoid secondary neurological deterioration. 3,8,10 Regarding surgical procedure, 2-above and 2-below segmental fixation using the double endplates penetrating screw could be applied in patients with DISH to secure rigid fixation as in this case. 12 Although it has been reported that functional improvement should not be expected once neurological impairment occurs, 8 our patient underwent immediate posterior fixation to prevent further SCI and enhance rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for treatment, early surgical fixation is recommended in patients with DISH-associated fractures complicated by neurological deficits or if instability is obvious or confirmed by additional stress imaging to avoid secondary neurological deterioration. 3,8,10 Regarding surgical procedure, 2-above and 2-below segmental fixation using the double endplates penetrating screw could be applied in patients with DISH to secure rigid fixation as in this case. 12 Although it has been reported that functional improvement should not be expected once neurological impairment occurs, 8 our patient underwent immediate posterior fixation to prevent further SCI and enhance rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 7 , 8 Some patients with this condition complain of only mild back pain or may not even notice back pain, which renders them reluctant to seek medical attention immediately after injury. 8 , 9 From the doctor’s standpoint, insufficient sharing of information about this condition among emergency physicians or primary care physicians may be responsible for a delayed diagnosis. 4 , 10 Non-specific tenderness of the back after a minor trauma would not warrant a thorough radiologic investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DISH, a condition previously not well recognized, has recently attracted attention and has been suggested to affect the surgical procedures for and treatment outcomes of various spinal diseases, including fractures and lumbar spinal canal stenosis. [6][7][8][9][10][11][12][13] Although lumbar spine X-ray is often performed in patients with low back pain or suspected lumbar spinal canal stenosis, thoracic spine X-ray and CT are performed less frequently due to lower incidence of thoracic spine diseases. The ability to infer the presence of DISH on plain X-ray images of the lumbar spine will allow for narrowing down of diseases to be screened and thereby reduce patients' exposure to radiation and medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…3 Clinical symptoms associated with DISH include back pain, limited range of motion, 4 decreased vital capacity, aspiration, and airway obstruction. 5 Other features characterized by recent reports include increased vulnerability to vertebral fracture, 6 difficulty in achieving bone fusion during conservative treatment after vertebral fracture, 7 high possibility of requiring surgery, 8 a risk factor for thoracic myelopathy, 9 increased risk of pseudarthrosis after lumbar spinal fusion, 10 and a poor prognostic factor due to a high reoperation rate after lumbar decompression surgery. [11][12][13] Hence, DISH affects the diagnosis, treatment, and posttreatment outcome of spinal diseases.…”
Section: Introductionmentioning
confidence: 99%